THE ROLE OF CYTOMEGALOVIRUS INFECTION AND EPSTEIN BAR VIRUS IN HUMAN PATHOLOGY - Rustamova G.R.; Samiyeva G.U.; Muhamadiyeva L.А. (Scholars Digest Publishing, 2023)
Cytomegalovirus infection (CMVI) is ubiquitous in nature. Usually has no age limit when affected, and is in the human body for a long time. In this case, a person can become infected immediately after birth. The infection may be present in the body and not cause disease or other pathologic symptoms [1].
Keywords: cytomegalovirus infection, tonsillitis, chronic adenoiditis, immune system, humoral immune system